Integration of Islamic Education into Early Childhood Education Education Curriculum: Building Character in the Digital Era - Ainnin, Iva Nur; Ismail, Ismail (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The character education model shows optimal impact when integrated into a holistic and integrative curriculum and learning. Today's children really need character education, in this case teachers and parents, especially teachers, play an important role in strengthening character education for their students. This study aims to examine the integration of Islamic education in the Early Childhood Education (PAUD) curriculum: Building Character in the Digital Era at Bina Putra Kledung Pacitan Kindergarten. This research method uses qualitative research. Descriptive analysis used in this study to explore the dynamics of learning and social interaction in the school environment. For data collection, the author used observation and interview methods with teachers, principals, and parents. The results of this study indicate that research on the integration of Islamic education in the PAUD curriculum at Bina Putra Kledung Pacitan Kindergarten shows that the holistic approach applied is effective in shaping children's character in the digital era.